Analysis of an mRNA exhibiting anomalous translational specificity. - Vellanoweth, R L (1991)
Gene 6 mRNA of Bacillus subtilis phage phi 29 is inefficiently translated under standard in vitro conditions by Escherichia coli, while it is efficiently translated by the in vitro system derived from B. subtilis. This is a rare example of the inability of E. coli to translate mRNA translated by B. subtilis. The ionic condition in the translation systems was the key component in the differential recognition of the gene 6 message by E. coli and B. subtilis ribosomes. Its translation by E. coli ribosomes was preferentially inhibited by moderate levels of KCl, while its translation by B. subtilis ribosomes was unaffected by these concentrations of salt. This preferential inhibition with E. coli ribosomes was observed in vitro as well as in vivo. While not influencing the general phenomenon of preferential inhibition, anion-specific effects were observed in overall protein synthesis. Glutamate and acetate promoted efficient synthesis over a broad range of concentrations, whereas chloride was inhibitory at all concentrations tested.